Cost comparison of five Australasian obesity prevention interventions for children aged from birth to two years. Issue 12 (18th June 2020) - Brown, Vicki; Tan, Eng J.; Hayes, Alison; Baur, Louise; Campbell, Karen; Taylor, Rachael; Byrne, Rebecca; Wen, Li Ming; Hesketh, Kylie D.; Moodie, Marjory
Summary: Background: In the absence of rigorous evidence of cost‐effectiveness for early childhood obesity prevention interventions, the next‐best option may be for decision‐makers to consider the relevant costs of interventions when allocating resources. Objectives: This study aimed to estimate systematically the cost of five obesity prevention interventions in children aged 0‐2 years, undertaken in research settings in Australia and New Zealand. Methods: A standardised costing protocol informed the costing methodology, ensuring comparability of results across interventions. Micro‐costing was undertaken, with intervention costs defined from the funder perspective and valued in 2018 Australian dollars using unit costs from the trials or market rates. Results: Interventions varied widely in their resource use. The total cost per participant ranged from 80 for the CHAT SMS intervention arm (95% UI 77‐82) to 1135 for the Healthy Beginnings intervention (95% UI 1059‐1189). Time costs of personnel delivering interventions contributed >50% of total intervention costs for all included studies. Conclusions: An understanding of the costs associated with intervention delivery modes is important, alongside effectiveness. Telephone delivery may include unexpected costs associated with connection to intervention participants at convenient times. A SMS‐based intervention had the lowest delivery cost in this study.